64.0k views
5 votes
Pls solve this as soon as possible

Pls solve this as soon as possible-example-1

1 Answer

5 votes

Answer:

x³ - y³ = 0

Explanation:

Given :
(x)/(y)+(y)/(x)=-1

To Find : value of (x³ - y³)

Since,
(x)/(y)+(y)/(x)=-1


(x^2+y^2)/(xy)=-1

x² + y² = -xy

x² + y² + xy = 0 -----(1)

Since, x³ - y³ = (x - y)(x² + xy + y²) [From the formula, (a³ - b³) = (a -b)(a²+ b² + ab)

= (x - y)(0) {From equation (1)]

= 0

Therefore, value of x³ - y³ = 0 will be the answer.

User Sphereinabox
by
5.5k points